Is telerehabilitation an effective maintenance strategy for patients with chronic obstructive pulmonary diseases: a systematic review - Uche-Okoye, Demelum (2023)
Pulmonary rehabilitation (PR) has proven to improve the physical and psychosocial function in patients with chronic obstructive pulmonary disease (COPD). However, the gains achieved during pulmonary rehabilitation diminish over time without an effective maintenance strategy. With several factors affecting access to pulmonary rehabilitation, calls for innovative models were made, which saw the emergence of studies exploring telerehabilitation (TR) as an alternative to traditional pulmonary rehabilitation models. Although there are current reviews exploring the effectiveness of telerehabilitation as an alternative for conventional PR, no review has considered telerehabilitation effectiveness in the long term. Hence, this review aims at examining the effectiveness of telerehabilitation following to pulmonary rehabilitation in patients with chronic obstructive pulmonary disease.